The efficacy of Rhinos® SR on nasal resistance and nasal symptoms in patients with perennial allergic rhinitis : a randomized, double-blind, placebo-controlled study (Faculty of Medicine Universitas Indonesia, 2008)
Rhinos® SR is a fixed combination of 5 mg loratadine and 60 mg pseudoephedrine immediate release and 60 mg pseudoephedrine sustained release. The present study was aimed to assess the efficacy of Rhinos® SR on nasal airway resistance (NAR) objectively using rhinomanometer and on nasal symptoms in patients with perennial allergic rhinitis (PAR) in a tropical country. This was a randomized, double-blind, parallel group study in 59 PAR patients who visited the ENT clinic at Dr. Soetomo General Hospital, Surabaya. Outpatients of both gender, having moderate to severe PAR for a minimal of 2 years, aged 12 years or older, with a total nasal symptom score (TNSS) > 6 and a nasal congestion score > 2, received Rhinos® SR or placebo twice daily for 7 days. The primary efficacy parameter was the decrease in the NAR values (measured by rhinomanometer on Day 1) of Rhinos® SR from those of placebo. The NAR values were calculated as the area under the curve (AUC) of NAR versus time. The secondary efficacy parameters were the percentage reduction of the clinical symptoms (nasal and nonnasal) evaluated by both the patient and the physician after 1 week use of Rhinos® SR or placebo. From 59 eligible patients, all completed this 1-week trial. For NAR values, after the baseline were considered as 100%, the AUC0-10 h were not significantly different between Rhinos® SR and placebo. However, as the pseudoephedrine reached its peak concentration, i.e. 2 hrs for the immediate release and 6 hrs for the sustained release, then AUC0-2 h and AUC0-6 h of Rhinos® SR were significantly lower compared to those of placebo. Total nasal symptom score (TNSS) evaluated by the patient (sum of the last 3 mornings) for Rhinos® SR decreased 33.0% from baseline (p < 0.001), for placebo decreased 21.9% from baseline (p = 0.002), but the decrease by Rhinos® SR was not significantly different from the decrease by placebo. TNSS evaluated by the physician, nasal congestion score (NCS) and total symptom score (TSS, total nasal and nonnasal), and even the individual symptom scores, evaluated by the patient and the physician, showed similar pattern, i.e. both Rhinos® SR and placebo decreased the symptoms significantly from baseline, and the decreases by Rhinos® SR were larger than the decreases by placebo, but the decreases by Rhinos® SR and placebo were not statistically different. No adverse event was found in this study. From the present study it was concluded that in patients with moderate to severe PAR in a tropical country, Rhinos® SR was effective in relieving nasal congestion by objective measurements of NAR. Rhinos® SR twice a day for 7 days was also effective in reducing the clinical symptoms of PAR although the reductions did not reach statistical significance compared to those by placebo, and was well tolerated. (Med J Indones 2008; 17: 114-26)